1998
DOI: 10.1364/ao.37.006871
|View full text |Cite
|
Sign up to set email alerts
|

Observation of high gain in a liquid-crystal panel with photoconducting polymeric layers

Abstract: A novel, to our knowledge, liquid-crystal panel suitable for real-time holographic purposes has been prepared. A nematic liquid-crystal layer sandwiched between photoconducting polymeric layers, when exposed to a sinusoidal light-intensity pattern, shows efficient formation of refractive-index gratings. The unique feature of the presented panel is its ability to switch energy from beam to beam in a manner similar to the charge-diffusion-controlled photorefractive effect. In a two-wave-mixing experiment multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…17 Finally, we have observed that cells with just one photoconductive layer were as efficient, in terms of two-beam coupling, as cells with two photoconductive layers, the design adopted in all earlier publications. 3,11,12 As expected, our experimental data on two-beam coupling, which we will present in detail in the following section, are in good agreement with previously published results. 3,11,12 Our data are also consistent with the results obtained in cells with nonphotoconducting polymer layers.…”
Section: Introductionsupporting
confidence: 92%
See 4 more Smart Citations
“…17 Finally, we have observed that cells with just one photoconductive layer were as efficient, in terms of two-beam coupling, as cells with two photoconductive layers, the design adopted in all earlier publications. 3,11,12 As expected, our experimental data on two-beam coupling, which we will present in detail in the following section, are in good agreement with previously published results. 3,11,12 Our data are also consistent with the results obtained in cells with nonphotoconducting polymer layers.…”
Section: Introductionsupporting
confidence: 92%
“…3,11,12 As expected, our experimental data on two-beam coupling, which we will present in detail in the following section, are in good agreement with previously published results. 3,11,12 Our data are also consistent with the results obtained in cells with nonphotoconducting polymer layers. 13 …”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations